Servicescapes: The Impact of Physical Surroundings on Customers and Employees - Bitner, Mary Jo (Journal of Marketing, 1992)
A typology of service organizations is presented and a conceptual framework is advanced for exploring the impact of physical surroundings on the behaviors of both customers and employees. The ability of the physical surroundings to facilitate achievement of organizational as well as marketing goals is explored. Literature from diverse disciplines provides theoretical grounding for the framework, which serves as a base for focused propositions. By examining the multiple strategic roles that physical surroundings can exert in service organizations, the author highlights key managerial and research implications.